A Review Paper on Big Data Analytics (International Journal of Innovative Research in Computer Science & Technology, 2022)
The information revolution gave decision  makers huge quantities of data available. Big data refers to  datasets that are not just large, but also significant in diversity  and speed and that make standard tools and approaches hard  to handle. Because such data is fast growing, solutions  should be explored and supplied so that these datasets are  able to handle and extract value and information. In  moreover, policymakers need to be able to get useful  understanding into such diverse and fast changing data, from  everyday transactions to contacts with customers and social  network information. The Big Data Analytics, the  deployment of advanced Big Data Analytics methodologies  can deliver this value. The purpose of the article is to  evaluate several analytical methods and means that may be  used for Big Data and the potential that Big Data Analytics  offers for the use of diverse decision-making areas.
Keywords: Analytics; Big data; Data mining; Datasets; Network